2002
DOI: 10.1002/jnm.457
|View full text |Cite
|
Sign up to set email alerts
|

An approach for the calculation of magnetic field within square spiral inductors at low frequency

Abstract: SUMMARYThe magnetic field distribution within a square spiral inductor is investigated in this paper by summing closed-form expressions for the fields from each segment. Plots illustrating the variation of the normally directed B-field penetrating the surface of the spiral traces are then developed for a variety of perspectives. The expressions and insight gained represent an essential step in developing a detailed model of effects such as current crowding, which significantly limit the spiral's performance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In an equilibrium state, the net ion flux through the membrane should be zero and the voltage difference built in between the membrane would also reach a critical value of −12 mV in HeLa cells [20] or −60 mV in PC-12 cells [21] where the intracellular voltage is a negative value relative to the extracellular one. In the signal transduction process, cationic electrosensitive channel-proteins play an important role in the generation of the potential gradients [22]. The electrostatic interaction between the voltage sensor in a voltage-gated channel and the transmembrane caused by the concentration difference of cations between the internal and external membrane will determine the switching voltage of the voltage-gated channel [23].…”
Section: Theory Of Biological Effects By Elf-emf Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In an equilibrium state, the net ion flux through the membrane should be zero and the voltage difference built in between the membrane would also reach a critical value of −12 mV in HeLa cells [20] or −60 mV in PC-12 cells [21] where the intracellular voltage is a negative value relative to the extracellular one. In the signal transduction process, cationic electrosensitive channel-proteins play an important role in the generation of the potential gradients [22]. The electrostatic interaction between the voltage sensor in a voltage-gated channel and the transmembrane caused by the concentration difference of cations between the internal and external membrane will determine the switching voltage of the voltage-gated channel [23].…”
Section: Theory Of Biological Effects By Elf-emf Exposurementioning
confidence: 99%
“…Figure 1(b) shows the simulation result indicating that a 60 Hz and 1.2 mT MF is built in the central region of the inductor with a 60 Hz, 150 mA electrical input current. Ibrahim et al [22] have shown that the adopted input current source with a frequency of 60 Hz can generate an ELF-MF which has the same field strength as that generated by a dc input. Thus, according to the concept of the quasielectrostatic current source associated with the Biot-Savart law, an analytical model for characterizing the strength of the time-variant MF built by the spiral inductor in terms of the geometrical structure and amplitude of an input current is derived and verified by the Ansoft-Maxwell simulation and experimental measurement in this work.…”
Section: Localized Elf-emf Platform Designmentioning
confidence: 99%